-6y2+24=0

Subtract 24 from both sides of the equation.

-6y2=-24

Divide each term in -6y2=-24 by -6.

-6y2-6=-24-6

Cancel the common factor of -6.

Cancel the common factor.

-6y2-6=-24-6

Divide y2 by 1.

y2=-24-6

y2=-24-6

Divide -24 by -6.

y2=4

y2=4

Take the square root of both sides of the equation to eliminate the exponent on the left side.

y=±4

Simplify the right side of the equation.

Rewrite 4 as 22.

y=±22

Pull terms out from under the radical, assuming positive real numbers.

y=±2

y=±2

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

y=2

Next, use the negative value of the ± to find the second solution.

y=-2

The complete solution is the result of both the positive and negative portions of the solution.

y=2,-2

y=2,-2

y=2,-2

Solve for y -6y^2+24=0